Neuroanatomy- and Pathology-Based Functional Examinations of Experimental Stroke in Rats: Development and Validation of a New Behavioral Scoring System - Yeh, Shin-Joe; Tang, Sung-Chun; Tsai, Li-Kai; Jeng, Jiann-Shing; Chen, Chi-Ling; Hsieh, Sung-Tsang (Frontiers in Behavioral Neuroscience, 2018)
In experimental stroke studies, a neuroanatomy-based functional examination of behaviors is critical to predict the pathological extent of infarcts because brain-imaging studies are not always available. However, there is a lack of systematic studies to examine the efficiency of a behavioral test for this purpose. Our work aimed to design a new score for this goal in stroke rats, by simplifying the Garcia score (with subscore 1-6) and adding circling as subscore 7. MRI and 2,3,5-triphenyltetrazolium chloride staining were used to determine the pathological extent after transient middle cerebral artery occlusion. The modified summations of subscores were designed according to the predictability of each subscore for locations and sizes of infarcts in one group of stroke rats, and were validated in another group. The original Garcia score was able to predict the pathological extent of edema-adjusted infarct size ≥ 30%, and the summation of subscore 4, 6, and 7 (4: climbing, 6: vibrissae sensation, 7: circling) also could predict it well. The original Garcia score failed to predict infarct at the primary motor cortex, while the summation of subscore 4, 6, and 7 potentially could predict not only the primary motor cortex, but also the forelimb, hindlimb and barrel field regions of the primary sensory cortex. Accordingly, this neuroanatomy-correlated functional assessment system composed of subscore 4, 6, and 7 was proposed, with less examination time and better inter-rater reliability than the original Garcia score. In summary, this new scoring system, summation (4,6,7) score, examined motor and sensory functions based on neuroanatomical involvement, having the potential to predict the pathological extent and specific relevant brain areas of infarcts, respectively.